2008
DOI: 10.1590/s1516-31802008000100009
|View full text |Cite
|
Sign up to set email alerts
|

Sudden infant death syndrome in Brazil: fact or fancy?

Abstract: CONTEXT AND OBJECTIVE: The true incidence of sudden infant death syndrome (SIDS) in Brazil is unknown. The aim here was to identify SIDS cases in the city of Ribeirão Preto, State of São Paulo, between 2000 and 2005, in order to estimate its incidence. DESIGN AND SETTING: Retrospective analysis of data on live births and infant deaths in Ribeirão Preto and from autopsies of infants performed at the Death Verification Service of the Interior (SVOI) between 2000 and 2005. RESULTS: There were 47,356 live births a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 24 publications
0
1
0
1
Order By: Relevance
“…Underdiagnosis may help explain this discrepancy because an earlier study found comparable rates of SIDS in Brazil and the United States, after adjusting for underdiagnosis (Nunes et al, 2001). On the other hand, a recent study using death certificates found much lower rates of SIDS in Brazil compared with the United States, suggesting that underdiagnosis may still contribute to Brazil's lower rates (Woida, Saggioro, Ferro, & Peres, 2008). Table 1 and for maternal smoking prevalence are from the confidence intervals of the estimates.…”
Section: Prevalence Of Adverse Mch Outcomes In Brazilmentioning
confidence: 99%
“…Underdiagnosis may help explain this discrepancy because an earlier study found comparable rates of SIDS in Brazil and the United States, after adjusting for underdiagnosis (Nunes et al, 2001). On the other hand, a recent study using death certificates found much lower rates of SIDS in Brazil compared with the United States, suggesting that underdiagnosis may still contribute to Brazil's lower rates (Woida, Saggioro, Ferro, & Peres, 2008). Table 1 and for maternal smoking prevalence are from the confidence intervals of the estimates.…”
Section: Prevalence Of Adverse Mch Outcomes In Brazilmentioning
confidence: 99%
“…2 No Brasil, não existem estatísticas oficiais sobre a incidência de SMSL, 3 mas estudos regionais revelaram uma taxa de mortalidade que varia de 0,13/1000 nascidos vivos a 0,45/1000 nascidos vivos. 4,5 Entretanto, evidências sugerem subnotificação dos casos em nosso país. 5 Inúmeros estudos propuseram causas e explicações fisiopatológicas para a SMSL, tais como obstrução das vias aéreas durante o sono seguida de reinalação dos gases expirados e coma hipóxico.…”
Section: Introductionunclassified